GROWTH, DEVELOPMENT AND PRODUCTIVITY OF OIL CROP IN IRRIGATED TYPICAL GRAY SOILS (Conferencea, 2023)
Nowadays, the increase in the world’s population means that the demand for food, including vegetable oil and protein products, is increasing day by day. Soybeans and sunflowers are the main source of raw materials in the vegetable oil production industry. “Today soybeans are grown on 122.1 million hectare and sunflower is grown 25.6 mln. Hectare on earth in the main and repeated periods. In terms of cultivated area, soy occupies the fourth place after wheat, rice and corn, and the annual gross grain yield is 220.6 million tons. Brazil, the USA and Argentina are the leading countries in the export of soybeans. China, Korea and other Asian countries are the main importing countries. Russia, China, Argentina, Romania and Ukraine are the leading countries in the cultivation of sunflowers, with an annual average of 40.5-42.0 million. tons of crops are grown. According to the international FAO, in 2020, 162 million tons of soybeans will be grown by 2030 in the world, and it is expected to increase by 371 mln. tons» For this, it is important to develop agrotechnology of soybean and sunflower cultivation as a repeated crop, including irrigation procedures.